An overview on climate change, environment, and innovative finance in emerging and developing economies - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2022)
The global economy has been facing a series of adverse shocks in recent years including the COVID-19 pandemic, climate crisis, the Russian invasion of Ukraine, high inflation, and interest rate shocks driven by global monetary policy normalization. The high cost of fossil fuels since 2021, moreover, has reminded the world that investment for clean energy projects has been severely inadequate due to limited implementation of climate policies and limited capital inflows to financing decarbonization efforts. While overdependence on fossil fuels might be inevitable currently, the world needs to accelerate transition to carbon neutrality and also begin to cope with nature capital stock and biodiversity losses, which are happening at an alarming pace. In particular, more financial support should be provided to emerging and developing economies (EMDEs) to help achieve climate and environmental goals and other sustainable development goals (SDGs). This paper takes an overview of some innovative finance schemes applicable to EMDEs, including blended finance to mobilize more private capital to climate and environmental projects and debt-for-climate swaps (or debt-for-nature swaps), to provide de facto grants to small high-debt economies in exchange for climate projects (or nature protection). The paper also provides some suggestions for further actions through better coordination among donor and recipient nations led by G7 and G20 nations.
Keywords: F34; F35; F64; G23; 330; public-private partnership; blended finance; debt-for-nature swaps; performance-based grants